2021
DOI: 10.1101/2021.08.19.456783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate predictions of individual differences in task-evoked brain activity from resting-state fMRI using a sparse ensemble learner

Abstract: Modelling and predicting individual differences in task-evoked FMRI activity can have a wide range of applications from basic to clinical neuroscience. It has been shown that models based on resting-state activity can have high predictive accuracy. Here we propose several improvements to such models. Using a sparse ensemble leaner, we show that (i) features extracted using Stochastic Probabilistic Functional Modes (sPROFUMO) outperform the previously proposed dual-regression approach, (ii) that the shape and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In efforts to improve the prediction of human behavior and brain activity from functional connectivity, most research to date focuses on model enhancement. This includes exploring different machine-learning algorithms and testing different model parameters (Ngo, Khosla, Jamison, Kuceyeski, & Sabuncu, 2021;Zheng et al, 2021). Here, we take an alternative data-centric approach and focus on enhancing the features rather than the model.…”
Section: Discussionmentioning
confidence: 99%
“…In efforts to improve the prediction of human behavior and brain activity from functional connectivity, most research to date focuses on model enhancement. This includes exploring different machine-learning algorithms and testing different model parameters (Ngo, Khosla, Jamison, Kuceyeski, & Sabuncu, 2021;Zheng et al, 2021). Here, we take an alternative data-centric approach and focus on enhancing the features rather than the model.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding how the brain changes its functionality in response to tasks/stimuli is of great interest and has a wide range of clinical applications 25 . For example, fMRI studies with an emotional task consistently showed abnormalities in the prefrontal cortex-limbic area in patients with anxiety disorders, who tend to overreact to emotional stimuli 26 .…”
Section: Comparison Of Resting-state and Task-evoked Functional Archi...mentioning
confidence: 99%